2022
DOI: 10.1038/s41420-022-01286-w
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH5 promotes PD-L1-mediated immune escape through m6A modification of ZDHHC3 in glioma

Abstract: N6-methylation of adenosine (m6A) is one of the most frequent chemical modifications in eukaryotic RNAs and plays a vital role in tumorigenesis and progression. Recently, emerging studies have shown that m6A modification by ALKBH5 was associated with immunotherapy response in various types of cancer. However, whether m6A demethylases ALKBH5 participate in regulating the tumor immune microenvironment and the efficacy of immunotherapy in glioblastoma remain unknown. Here, we found that deletion of ALKBH5 signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…We next explored potential key molecular targets for the inhibition of pancreatic cancer growth after knockdown of ZDHHC3. Previous studies have shown that ZDHHC3 palmitoylates PD-L1 to maintain its protein stability in colon cancer and gliomas [ 23 , 46 ]. We next sought to determine whether ZDHHC3 influences cancer immunity by regulating PD-L1 expression in pancreatic cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…We next explored potential key molecular targets for the inhibition of pancreatic cancer growth after knockdown of ZDHHC3. Previous studies have shown that ZDHHC3 palmitoylates PD-L1 to maintain its protein stability in colon cancer and gliomas [ 23 , 46 ]. We next sought to determine whether ZDHHC3 influences cancer immunity by regulating PD-L1 expression in pancreatic cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the role of YTHDF2 as an m6A “reader,” we carried out MeRIP‐seq in NOZ cells to detect the distribution of m6A modification and found that most of the m6A peaks were highly enriched in the 3′‐UTR of mRNAs (Figure 5E). A motif search identified a consensus sequence motif, GGAC, within the m6A peak region (Figure 5F), which is consistent with previous findings 24,25 …”
Section: Resultssupporting
confidence: 90%
“…A motif search identified a consensus sequence motif, GGAC, within the m6A peak region (Figure 5F), which is consistent with previous findings. 24,25 To identify the potential target mRNAs directly bounded by YTHDF2, anti-YTHDF2 RIP-seq was then carried out in NOZ cells with two replicates, and a total of 1502 genes were obtained (Figure 5G). YTHDF2 primarily acts by selectively binding to m6A-modified mRNAs and mediating their deadenylation.…”
Section: Identification Of the Ythdf2 Downstream Target By Multi-omic...mentioning
confidence: 99%
“…Studies have confirmed the significant correlation of ALKBH5 with PD‐L1 in clinical intrahepatic cholangiocarcinoma specimens research 73 . Further studies found that the knockdown of ALKBH5 promotes the m6A level of PD‐L1 and accelerates mRNA degradation of PD‐L1 in a YTHDF2‐dependent manner in glioma 74 . Interestingly, impairing the expression level of ALKBH5 decreases PD‐L1 not only in cancer cells but also in monocytes/macrophages, suggesting that ALKBH5 can manipulate PD‐L1 by influencing the tumor immune microenvironment.…”
Section: The M6a Rna Methylation In Pd‐l1mentioning
confidence: 61%
“…73 Further studies found that the knockdown of ALKBH5 promotes the m6A level of PD-L1 and accelerates mRNA degradation of PD-L1 in a YTHDF2-dependent manner in glioma. 74 Interestingly, impairing the expression level of ALKBH5 decreases PD-L1 not only in cancer cells but also in monocytes/macrophages, suggesting that ALKBH5 can manipulate PD-L1 by influencing the tumor immune microenvironment. However, the specific mechanism is still undefined.…”
Section: Erasermentioning
confidence: 98%